2020
DOI: 10.18502/ijdo.v12i3.4444
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Glomerular Filtration Rate with Coronary Artery Disease in Type 2 Diabetic Patients

Abstract: Objective: Diabetes mellitus is a chronic illness and adherence to medications is vital to manage the illness. The purpose of this study was to examine the prediction of medication adherence based on personality factors in a group of individuals with type 2 diabetes in Yasuj. Materials and Methods: One hundred twenty individuals with type 2 diabetes who visited health centers were selected for this study through convenience sampling. The participants completed the NEO-Five Factor Inventory and Medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Lin et al reported that TC, LDL‐C, and non‐HDL‐C levels were higher at lower GFR levels than in the GFR≥90 mL/min/1.73 m 2 13 . Samimagham et al showed that among patients with T2D, patients with eGFR≤60 mL/min/1.73 m 2 had higher TG levels than eGFR>60 mL/min/1.73 m 2 14 . In contrast, Lin et al showed that among patients with T2D, patients with decreased eGFR had lower median LDL‐C than the higher eGFR group 16 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lin et al reported that TC, LDL‐C, and non‐HDL‐C levels were higher at lower GFR levels than in the GFR≥90 mL/min/1.73 m 2 13 . Samimagham et al showed that among patients with T2D, patients with eGFR≤60 mL/min/1.73 m 2 had higher TG levels than eGFR>60 mL/min/1.73 m 2 14 . In contrast, Lin et al showed that among patients with T2D, patients with decreased eGFR had lower median LDL‐C than the higher eGFR group 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al showed that LDL‐C levels had a positive correlation, and TG levels were negatively correlated with eGFR 16 . Samimagham et al reported an inverse correlation between eGFR and TG levels 14 . Hirano et al reported that eGFR was positively correlated with HDL‐C, and after adjustment, eGFR was negatively associated with TC and non‐HDL‐C 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They believed that this is related to the narrow range of blood pressure among participants and these populations had normal blood pressure levels. But Samigham et al, demonstrated a significant association between history of hypertension and GFR<60 [20]. James et al, reported that lower GFR was associated with higher risks of acute kidney injury in patients with and without diabetes or hypertension [21].…”
Section: Discussionmentioning
confidence: 99%